Mães da periferia entre luta e luto: práticas de resistência e cuidado de mulheres que tiveram filhos/as assassinados/as no Ceará - Rodrigues, Jéssica da Silva (2022)
This thesis study analyzes how a collective of women who had their children murdered/victims of state violence has operated in the production of resistance, care and reconstruction of the trajectories of its participants. The study was carried out with the group “Mães da Periferia”, a collective composed mainly of women who had their children murdered by police violence in the State of Ceará. More specifically, the research reflects how the aforementioned group coengenders mourning and struggle processes from the creation of care strategies; it problematizes how the group operates the construction of memory, justice, reparation based on its practices of resistance and discusses what effects the collective produces in the trajectory of the women that integrate it. The reflections proposed here are anchored in references from feminist studies, especially from black and decolonial feminism such as Curiel, Davis, Akotirene, Nogueira, Mayorga, Menezes, Gonzalez, Carneiro, Bento, hooks, Lugones; in dialogues with authors from anti-colonial perspectives such as Mbembe and Fanon. These authors help us to think about issues of race, class and gender in an anti-colonial and intersectional perspective, in connection with psychology. Thus, they make it possible for us to reflect on the marks of coloniality and the violence that are immanent in the trajectories of struggle and mourning of these women. Methodologically, the study is characterized as qualitative, in line with the decolonial intersectional participatory perspective. The following methodological strategies were used: 1) Carrying out a group device with the participants of the collective “Mães da Periferia”, as a light care technology; 2) Conducting narrative interviews with mothers from the collective, in order to hear the dimension of singularity in their processes of struggle for justice and memory of their children, as well as aspects of their experiences. As tools, the following were used: Field Diaries and a semi-structured script for carrying out the interviews. As main results, it can be highlighted that women develop important care technologies among themselves; care has an important political dimension to itas it is directly related to ways of making life possible in the face of precarious policies for black bodies who experience forms of subalternization; forms of care are directly related to the processes of struggle for memory, justice and reparation; the transformation of mourning into struggles enables the continuity of life that asserts itself as a confrontation with death policies.